Bantuan Luar Negeri dan Pembangunan Berkelanjutan di Indonesia: Antara Ketergantungan dan Kemandirian - Bunga Sausan Sabilla; Herly Febri Fathiha; Nur Azmi Rahmadhini (Lembaga Pengembangan Kinerja Dosen, 2025)
Although foreign aid has played an important role in Indonesia's economic growth, dependence on foreign aid may hinder efforts to achieve national self-reliance. The purpose of this study is to look at how foreign aid contributes to sustainable development and the consequences of Indonesia's reliance on economic and technological independence. A qualitative approach using a literature review that includes books, journal articles and government documents is the methodology used. The research findings show that while foreign aid improves human resource capacity and accelerates infrastructure development, it also fosters continued dependency, hinders domestic technological advancement, and weakens local innovation capabilities. Particularly in the energy industry, Indonesia continues to rely on imported technologies, and faces barriers in terms of skills transfer from donor countries. Therefore, this article suggests that a national plan be implemented with an emphasis on local capacity building, research and development funding, and cooperation between the industrial and academic sectors. In conclusion, Indonesia must increase its economic and technological independence and reduce dependence on foreign aid to achieve sustainable development.